Management strategies to mitigate drought stress in Indian mustard (Brassica juncea L.) through microbes: Management strategies to mitigate drought stress in Indian mustard (Brassica juncea L.) through microbes - O P PREMI; IBANDALIN MAWLONG; SANGEETA PAUL; P K RAI (Journal of Oilseeds Research, 2020)
One irrigation schedule produced statistically similar seed yield of mustard as produced with two irrigations. One irrigation could be saved by using these cultures. Among the cultures, MRD17 and MKS6 gave 29.7% and 24.7% higher productivity over no inoculation. The other parameters such as relative water content, membrane stability index and chlorophyll content were also higher in these treatments.